Effect of asiatic and ursolic acids on morphology, hydrophobicity, and adhesion of UPECs to uroepithelial cells - Dorota, Wojnicz; Marta, Kicia; Dorota, Tichaczek-Goska (Folia microbiologica, 2013)
Adhesion of bacteria to epithelial tissue is an essential step in the progression of the urinary tract infections. Reduction of virulence factors responsible for microbial attachment may help to decrease or inhibit colonization of the host organism by pathogens. In the age of increasing bacterial antibiotic resistance, more and more attention is being paid to the use of plants and/or their bioactive components in the prevention and treatment of human infections. Asiatic acid (AA) and ursolic acid (UA), two plant secondary metabolites, were used as potential antibacterial agents. The current study aimed to determine the possible impact of AA and UA on morphology, hydrophobicity, and adhesion of clinical uropathogenic Escherichia coli strains (UPEC) to the uroepithelial cells. Our work describes for the first time the effects exerted by AA and UA on virulence factors of UPECs. The impact of both acids on the cell surface hydrophobicity of the investigated strains was very weak. The results clearly show the influence of AA and UA on the presence of P fimbriae and curli fibers, morphology of the UPECs cells and their adhesion to epithelium; however, some differences between activities of AA and UA were found.
Keywords: Anti-Bacterial Agents; Pentacyclic Triterpenes; uropatogenní Escherichia coli; Urothelium; Humans; lidé; Microbial Sensitivity Tests; sekvenční analýza DNA; hydrofobní a hydrofilní interakce; epitelové buňky; Hydrophobic and Hydrophilic Interactions; Sequence Analysis, DNA; pentacyklické triterpeny; rostlinné extrakty; Virulence Factors; Female; Uropathogenic Escherichia coli; fylogeneze; urotel; Cells, Cultured; mikrobiální testy citlivosti; antibakteriální látky; Bacterial Adhesion; kyselina ursolová; triterpeny; ženské pohlaví; bakteriální adheze; Plant Extracts; kultivované buňky; Epithelial Cells; Ursolic Acid; faktory virulence; Phylogeny; Triterpenes